TA'TSIR AL-BI'AH AL-LUGHAWIYAH 'ALA TA'LIM AL-LUGHAH AL-'ARABIYAH WA TA'ALLUMIHA LI AL-NATHIQIN BI GHAIRIHA - Mirwan Akhmad Taufiq (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2020)
This study aims to discover the effect of language environment on learning the Arabic language held in Indonesia and Sudan and also to identify the patterns of influence in the acquisition of the Arabic language. In this study, the researcher used the analytical and comparative descriptive method by using various tools: oral and written test for Southeast Asian students who are learning the Arabic language in the Center for Language Development in Indonesia and the Institute of Arabic Language in Sudan. The interview was held to some experts in Arabic teaching who had academic experience in both environments. From this research, it is found that the difference between both environments in the effect is very low; the Indonesian environment may affect students more active than average students in the Sudanese environment. Active learning and active acquisition may remove these environmental boundaries and enables them to improve their Arabic language skills.